Activation of miR-21 by STAT3 induces proliferation and suppresses apoptosis in nasopharyngeal carcinoma by targeting PTEN gene. - Hesheng Ou; Yumei Li; Min Kang (PLoS ONE, 2014)
The present study is to investigate the role of microRNA-21 (miR-21) in nasopharyngeal carcinoma (NPC) and the mechanisms of regulation of PTEN by miR-21. Fifty-four tissue samples were collected from 42 patients with NPC and 12 healthy controls. Human NPC cell lines CNE-1, CNE-2, TWO3 and C666-1 were used for cell assays. To investigate the expression of miR-21, RT-PCR was employed. RT-PCR, Western blotting, and immunohistochemistry were used to measure the expression of STAT3 mRNA and STAT3 protein. To test the effect of miR-21 on the cell growth and apoptosis of NPC cells in vitro, transfection of CNE1 and CNE2 cell lines and flow cytometry were performed. TUNEL assay was used to detect DNA fragmentation. To validate whether miR-21 directly recognizes the 3'-UTRs of PTEN mRNA, luciferase reporter assay was employed. miR-21 expression was increased in NPC tissues compared with control and the same result was found in NPC cell lines. Notably, increased expression of miR-21 was directly related to advanced clinical stage and lymph node metastasis. STAT3, a transcription factor activated by IL-6, directly activated miR-21 in transformed NPC cell lines. Furthermore, miR-21 markedly inhibited PTEN tumor suppressor, leading to increased AKT activity. Both in vitro and in vivo assays revealed that miR-21 enhanced NPC cell proliferation and suppressed apoptosis. miR-21, activated by STAT3, induced proliferation and suppressed apoptosis in NPC by targeting PTEN-AKT pathway.